Rural education in Colombia: experiences and perspectives - Martha Lucia Carrero Arango; María Fernanda González Rodríguez (Corporación Universitaria Minuto de Dios, 2017)
This article presents a reflection about the situation of the rural education in Colombia, its contributions to the education, its relation with the education in technologies and some educational experiences in the municipality of Ciudad Bolívar.